Investigations of the bioavailability/bioequivalence of topical corticosteroid formulations containing clobetasol propionate using the human skin blanching assay, tape stripping and microdialysis - Au, Wai Ling (Rhodes University, Faculty of Pharmacy, Pharmacy, 2010)
Currently, clinical trials in patients are required by most regulatory authorities for the assessment of bioequivalence of topical products where the drug is not intended for systemic absorption. Hence there is a dire need for suitable methods for the assessment of bioavailability and bioequivalence of such products since clinical safety and efficacy studies are expensive, time-consuming and require very large numbers of patients. Except for topical corticosteroid products where the human skin blanching assay/vasoconstrictor assay has been approved by the US FDA for bioequivalence assessment of those products, no other method has been "officially" approved for use in those investigations. However, a few alternative methods such as tape stripping and microdialysis have been pursued and considered to have the potential for use in ioequivalence/bioavailability studies. The human skin blanching assay was used to assess the bioequivalence of commercially available topical products containing 0.05% clobetasol propionate. Both visual and chromameter data were obtained and a commercially available topical corticosteroid product, Dermovate® cream was used as both the "Test" and the "Reference" product. The results indicated that both visual and chromametric assessments were comparable to each other and that either could be used for the assessment of the bioequivalence of topical products containing clobetasol propionate. The screening procedure was optimized to identify potential "detectors" for inclusion in the bioequivalence studies. This resulted in fewer subjects being required in a bioequivalence pivotal study, still having the necessary power to confirm bioequivalence using the human skin blanching assay. Another objective of this research was to re-visit tape stripping and other possible alternative methods such as dermal microdialysis and to optimize these procedures for bioequivalence assessment of topical formulations where the drug is not intended for systemic absorption. In the past few decades, tape stripping has been used to investigate bioavailability/bioequivalence of various topical formulations. This technique involves the removal of the stratum corneum to assess drug penetration through the skin. A draft FDA guidance for tape stripping was initially published but was subsequently withdrawn due to high variability and poor reproducibility. This research project used an optimized tape stripping procedure to determine bioavailability and establish bioequivalence between three commercially available formulations containing 0.05 % m/m clobetasol propionate. Furthermore, tape stripping was validated by undertaking a study to assess the bioequivalence of a 0.05% topical cream formulation (Dermovate® cream) using the same cream as both the "Test" and "Reference" product, in which bioequivalence was confirmed. The findings highlight the potential of tape stripping as an alternative method for the assessment of bioequivalence of clobetasol propionate formulations and may possibly be extended for use in other topical products. Microdialysis is another useful technique that can assess the penetration of topically applied substances which diffuses through the stratum corneum and into the dermis. Microdialysis has previously been successfully used for in vivo bioavailability and bioequivalence assessments of topical formulations. However, the drugs which were under investigation were all hydrophilic in nature. A major problem with the use of microdialysis for the assessment of lipophilic substances is the binding/adherence of the substance to the membrane and other components of the microdialysis system. As a result, this necessitates the development of a microdialysis system which can be used to assess lipophilic drugs. Intralipid® 20% was investigated and successfully utilized as a perfusate to recover a lipophilic topical corticosteroid, clobetasol propionate, in microdialysis studies. Hence, the bioavailability of clobetasol propionate from an extemporaneous preparation was determined in healthy human volunteers using microdialysis. These findings indicate that in vivo microdialysis can be used to assess lipophilic drug penetration through the skin. A novel approach to investigate drug release from topical formulations containing 0.05% clobetasol propionate using in vitro microdialysis was also undertaken. The in vitro findings were found to be in agreement with the results obtained using tape stripping to assess bioequivalence of the same commercially available products, namely Dermovate® cream, Dovate® Cream and Dermovate® ointment. These results indicate the potential to correlate in vitro with in vivo data for bioequivalence assessment of such topical dosage forms.
Keywords: Adrenocortical hormones -- Bioavailability; Drugs -- Therapeutic equivalency; Adrenocortical hormones -- Effectiveness; Adrenocortical hormones -- Testing; Adrenocortical hormones -- Side effects; Transdermal medication